Torquetenovirus detection in exosomes enriched vesicles circulating in human plasma samples - Martelli, Francesco; Macera, Lisa; Spezia, Pietro Giorgio; Medici, Chiara; Pistello, Mauro; Guasti, Daniele; Romagnoli, Paolo; Maggi, Fabrizio; Giannecchini, Simone (Virology journal, 2018)
Torquetenovirus (TTV) belongs to Anelloviridae family, infects nearly all people indefinitely without causing overt disease establishing a fine and successful interaction with the host. Increasing evidence have shown some human viruses exploit extracellular vesicles thereby helping viral persistence in the host. Here, the presence of TTV in extracellular vesicles circulating in human plasma was investigated. TTV DNA was quantified in plasma-derived exosomes from 122 samples collected from 97 diseased patients and 25 healthy donors. Exosomes enriched vesicles (EEVs) were extracted from plasma and characterized by Nanoparticle tracking analysis, by western blot for presence of tetraspanin CD63, CD81 and annexin II protein and, finally, by electron microscopy (EM). Presence and quantitation of TTV DNA were assessed with an universal single step real-time TaqMan PCR assay. Preliminary investigation showed that the human plasma extracted extracellular vesicles exhibited a main size of 70 nm, had concentration of 2.5 × 10 /ml, and scored positive for tetraspanin CD63, CD81 and annexin II, typical characteristic of the exosomes vesicles. EEVs extracted from pooled plasma with TTV DNA viremia of 9.7 × 10 copies/ml showed to contain 6.3 × 10 TTV copies/ml, corresponding to 0.65% of total viral load. Important, TTV yield changed significantly following freezing/thawing, detergents and DNAse treatment of plasma before EEVs extraction. EEVs purified by sucrose-density gradient centrifugation and analysis of gradient fraction positive for exosomes marker CD63 harbored 10 TTV copies/ml. Moreover, EM evidenced the presence of TTV-like particles in EEVs. Successive investigation of plasma EEVs from 122 subjects (37 HIV-positive, 20 HCV infected, 20 HBV infected, 20 kidney transplant recipients, and 25 healthy) reported TTV DNA detection in 42 (34%) of the viremic samples (37 were from diseased patients and 5 from healthy people) at a mean level of 4.8 × 10 copies/ml. The examination of EEVs selected samples reported the presence of TTV genogroup 1, 3, 4 and 5, with genogroup 3 highly observed. Collectively, although these observations should be confirmed by further studies, circulation of TTV particles in EEVs opens new avenues and mechanistic insights on the molecular strategies adopted by anelloviruses to persist in the host.